Impact Of Pour Point Depressant Enhanced With Graphene Oxide On Thermal And Microstructure Properties Of Simulated Crude Oil Model - Mohd Johary, Muhammad Danial (Universiti Sains Malaysia, 2018)
Different lateral size of Graphene oxide (GO) reduce by sonication were comparatively investigated as additive for PPD to improve the flow ability of crude oil simulated crude oil model. The GO was divided into 5 categories ,which is different in sonication time. The GO1, GO2, GO3, GO4, GO5 were sonicated at different time which is 0 min,10 min,30 min,60 min and 100 min respectively. The GO1 will be the control sample , as a bench mark of the result. The preparation of the emulsified PPD begin with the preparation of water-based solution which include the GO and oil-based solution, together both of the solution stirrer in the water bath. Furthermore, the morphology properties of sonicated GO were investigated using scanning electron microscopy (SEM) and, Fourier-transform infrared (FTIR) .From SEM image it seems as reduction lateral size of GO as increase the sonication time. Sonicated GO surface properties was confirmed by the FTIR results that show the same peak pattern from control sample. The stability test are conducted about 4 weeks ,the particle size of the sample increased by freeze thawed activities, but does not affect the stability of the emulsion. The zeta potential is about (-50mV - -60 mV) showing that the emulsion is in the stable range. The image of the crystal formation was studied. The heterogeneous nucleation mechanism, uniform and rod-like shape crystals were observed by polarizing optical microscopy ,the POM image showing that ,when present of GO it will delay the formation of wax crystal and tendency to form rod like instead of flake like at low temperature ,the smaller size of GO will exhibit good dispersion in the simulated crude oil. For further study on crystal formation, the dynamic changes of crystal structure network were taken apart in this study. The thermal study was conducted using Differential Scanning Calorimetry (DSC),that shows the improving the Wax Appearance Temperature (WAT) when adding the smaller lateral size of GO but higher from the blank sample (pure paraffin wax).The surface of the simulated crude oil was study using Scanning Electron Microscopy (SEM) ,The surface of the blank sample show wavy pattern ,this due to the formation of the 3D structure network, for Emulsified Jaypol Graphene Oxide 5 (EJGO5) show the surface like a human skin ,which is GO act as well distributed nucleation site .The pour point performance of Nano-hybrid PPD was improved compared with Emulsified Normal PPD (EJN) The increasing trends of performance by reducing lateral size of GO showing that the GO lateral size is the most influenced factor that increased pour point and flow ability performance of Emulsified PPD.